2015
DOI: 10.5901/mjss.2015.v6n5p175
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Brand Personality and Consumers’ Personality among Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ghorbani and Mousavi [90] revealed positive relations between conscientiousness and competence and between conscientiousness, extraversion, and excitement. The results of Anvari and Irum [91] are less meaningful; the authors found positive relations between all personality traits and all brand personality traits. Because the results of Anvari and Irum [91] do not reveal any specific relationships between consumer and brand personality, their results will be skipped in further research here.…”
Section: Consumer Personality and Brand Personality: Operationalization And Relationshipsmentioning
confidence: 73%
See 1 more Smart Citation
“…Ghorbani and Mousavi [90] revealed positive relations between conscientiousness and competence and between conscientiousness, extraversion, and excitement. The results of Anvari and Irum [91] are less meaningful; the authors found positive relations between all personality traits and all brand personality traits. Because the results of Anvari and Irum [91] do not reveal any specific relationships between consumer and brand personality, their results will be skipped in further research here.…”
Section: Consumer Personality and Brand Personality: Operationalization And Relationshipsmentioning
confidence: 73%
“…The results of Anvari and Irum [91] are less meaningful; the authors found positive relations between all personality traits and all brand personality traits. Because the results of Anvari and Irum [91] do not reveal any specific relationships between consumer and brand personality, their results will be skipped in further research here. Table 1 yields an overview of positive relationships between consumers' personality traits (measured by the five-factor model) and brand personality dimensions (measured by Aaker's [16] scale) that were discussed before.…”
Section: Consumer Personality and Brand Personality: Operationalization And Relationshipsmentioning
confidence: 73%
“…Similar studies in the Southeast Asian markets are no exception (e.g. Anvari & Irum, 2015;Balakrishnan, Lee, Shuaib, & Marmaya, 2009;Hashim, Mohtar, Che-Ha, & Taha, 2008). Personality and cultural psychology has long recognized that personality scales (i.e.…”
Section: Introductionmentioning
confidence: 71%
“…Specifically, studies have difficulty extracting a few of the original dimensions for example ruggedness dimension in other markets (Leonard and Katsanis, 2013;Valette-Florence and De Barnier, 2013). Similar studies in the Southeast Asian markets are no exception (Anvari and Irum, 2015;Balakrishnan et al, 2009;Hashim et al, 2008). Personality and cultural psychology has long recognized that personality scales (i.e.…”
Section: Introductionmentioning
confidence: 97%